2022
DOI: 10.1002/jctb.7049
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and catalytic behaviour of nano‐bimetallic nickel oxide on the thermal decomposition of dihydroxylammonium‐5,5′‐bistetrazole‐1,1′‐diolate

Abstract: Synthesis, characterization, and catalytic behaviour of nano-bimetallic nickel oxide on the thermal decomposition of dihydroxylammonium-5,5 0 -bistetrazole-1,1 0 -diolate)Bimetal combustion catalyst has become an emerging field in recent years, which is still in its infancy. When the combustion catalyst is used in double-base propellants, it can produce effects that conventional catalysts cannot achieve. In this study, nano-bimetallic nickel oxides (nanospheres of NiFe 2 O 4 and the sub-nanometre flower NiCo 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Metal oxides, as the largest branch of metal derivatives, possess attributes such as low dosage and remarkable efficacy, enabling them to achieve catalytic effects beyond the reach of traditional catalysts. Fe 2 O 3 is commonly used as an energetic material catalyst in metal oxides. Research found that Fe 2 O 3 has an excellent catalytic effect on the thermal decomposition process of TKX-50 .…”
Section: Effect Of Different Catalysts On Thermal Decomposition Of Tk...mentioning
confidence: 99%
See 3 more Smart Citations
“…Metal oxides, as the largest branch of metal derivatives, possess attributes such as low dosage and remarkable efficacy, enabling them to achieve catalytic effects beyond the reach of traditional catalysts. Fe 2 O 3 is commonly used as an energetic material catalyst in metal oxides. Research found that Fe 2 O 3 has an excellent catalytic effect on the thermal decomposition process of TKX-50 .…”
Section: Effect Of Different Catalysts On Thermal Decomposition Of Tk...mentioning
confidence: 99%
“…(Reprinted with permission from ref , 2019 Nature Publishing Group.) TGA (c) and DSC (d) curves of NiFe 2 O 4 and NiCo 2 O 4 with TKX-50 . (Reprinted with permission from ref , 2022 John Wiley & Sons, Inc.)…”
Section: Effect Of Different Catalysts On Thermal Decomposition Of Tk...mentioning
confidence: 99%
See 2 more Smart Citations